Qualidade de vida das pessoas surdas que se comunicam pela língua de sinais: construção da versão em libras dos instrumentos WHOQOL-BREF e WHOQOL-DIS - CHAVEIRO, Neuma (2011)
Introduction: The evaluation of the quality of life of the deaf community is limited by the difficulties of communication in the oral and written language, thence the necessity of developing reliable instruments in sign language with methodological strictness that includes particular characteristics of the deaf people. Among the cultural lines of the deaf community, sign language is the most emphasized one: besides being a linguistical system, it is an element of constitution of the deaf person identity. In Brazil, it is legally assured the deaf the right to communicate in his natural language, that is, Brazilian Sign Language (LIBRAS), with no imposition of the usage of the majority language of the country. This doctoring thesis is part of the WHOQOL-LIBRAS project, a result of a partnership between Federal University of Goiás, World Health Organization and Brazil´s WHOQOL group in Federal University of Rio Grande Do Sul. In order to perform the WHOQOL-LIBRAS project, it was divided into two sub-projects with distinct but interdependent stages: Project 1 - Construction of the WHOQOL-BREF and WHOQOL-DIS versions in LIBRAS; Project 2 - Application/validation of the WHOQOL-BREF and WHOQOL-DIS instruments in the LIBRAS version. This thesis comprises Project 1. General Objective: Build the LIBRAS version of the WHOQOL-BREF and WHOQOL-DIS instruments to evaluate the brazilian deaf community quality of life. Methods: A transversal and exploratory study, designing based in the Methodological Research. The methodology proposed by the World Health Organization was used and adapted to the deaf community, and in accordance with the criteria established with Brazil WHOQOL group, the accomplishment of the project was divided into 13 phases: 1. creation of the QUALITY OF LIFE sign; 2. development of the answer scales in LIBRAS; 3. translation by a bilingual group; 4. recouncilling version; 5. first retrotranslation; 6. production of the version in LIBRAS to be provided to the focal groups; 7. realization of the Focal Groups; 8. review by a monolingual group; 9. revision by the bilingual group; 10. semantic/syntactic analysis and second retrotranslation; 11. re-evaluation of the retrotranslation by the bilingual group; 12. recording the final version into the software in studio; 13. software development of the WHOQOL-BREF and WHOQOL-DIS instruments into the LIBRAS version. Results: Peculiar characteristics of the deaf people culture pointed to the necessity of adaptations in the application methodology of focal groups when it is compound by deaf people. The writing conventions of the signed languages are yet not consolidated, thus, some difficulties were faced in graphically register the translation phases of Portuguese into LIBRAS. Linguistics structures that caused major problems in translation were those that included portuguese idiomatic expressions, for many of them are no equivalent concepts between Portuguese and LIBRAS. In the end, it was possible to build up a WHOQOL-BREF and WHOQOL-DIS software in LIBRAS. Conclusion: The WHOQOL-BREF and the WHOQOL-DIS in LIBRAS will allow the deaf to express about the quality of life in an autonomous way, and this will make possible to investigate more accurately the issues of deaf people quality of live. Besides, the WHOQOL-BREF and the WHOQOL-DIS in LIBRAS will be part of the World Health Organization instruments for evaluating quality of life.